Competition and bank risk: the effect of securitization and bank capital - David Marqués-Ibá\~nez; Yener Altunbas; Michiel van Leuvensteijn (European Central Bank (ECB), 2014)
We find that the increased use of securitisation activity in the banking sector prior to the 2007- 2009 crisis augmented the effect of competition on realised bank risk (i.e. more intense competition and greater use of securitisation is correlated with higher levels of realised risk) during the crisis. In contrast, higher levels of capital did not buffer the impact of competition on realised risk. It follows that cooperation between supervisory and competition authorities is warranted to account for the stability implications of financial innovation and capital regulation.
Keywords: G21; D22; 330; bank risk; competition; securitisation